2010
DOI: 10.1002/cbic.201000341
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis by Dihydrofolate Reductase from the Psychropiezophile Moritella profunda

Abstract: The influence of temperature and pH on the stability and catalytic activity of dihydrofolate reductase (MpDHFR) from the cold-adapted deep-sea bacterium Moritella profunda was studied. The thermal melting temperature was found to be ∼38 °C and was not affected by pH, while activity measurements demonstrated that its stability was maximal at pH 7 and was reduced dramatically below pH 6 or above pH 8. The steady-state rate constant (k(cat)) was maximal at neutral pH and higher temperatures, while the Michaelis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(72 citation statements)
references
References 47 publications
10
61
1
Order By: Relevance
“…For instance, "Candidatus Scalindua" and other related anammox bacteria were previously found in oil fields with temperatures ranging from 55 to 75°C (73). The psychropiezophile Moritella profunda was found in regions of high pressure and cold temperatures (74), but a recent study demonstrated that the enzyme dihydrofolate reductase in Moritella profunda has subtle structural changes that allow it to remain active under high pressure and temperatures up to 80°C (75).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, "Candidatus Scalindua" and other related anammox bacteria were previously found in oil fields with temperatures ranging from 55 to 75°C (73). The psychropiezophile Moritella profunda was found in regions of high pressure and cold temperatures (74), but a recent study demonstrated that the enzyme dihydrofolate reductase in Moritella profunda has subtle structural changes that allow it to remain active under high pressure and temperatures up to 80°C (75).…”
Section: Discussionmentioning
confidence: 99%
“…Electrospray ionization mass spectrometry was used to determine the degree of isotopic substitution in the heavy enzyme, and structural integrity was confirmed by circular dichroism spectroscopy. Steady-state and stoppedflow kinetic measurements were performed as previously described (38,59). …”
Section: Methodsmentioning
confidence: 99%
“…25 The BsDHFR gene was purchased from Epoch Biolabs. Mutagenic primers for generating BsDHFR-L20M, BsDHFR-A104Q, BsDHFR-P122E, and BsDHFR-P129D were 5′-GTAAGGATAACCGC A TGCCGTGGCACCTGC-3′, 5′-CGCAGAGCTGTTTCGC CA GACCATGCCGATTGTC-3′, 5′-CTAAGATCTTTGCATCTTTC GA AGGGGATACTTTCTATCCAC-3′, and 5′-GGGGATACTTTCTATCCA GA TATTTCTGATGACGAATGG-3′, respectively (changes underlined).…”
Section: Methodsmentioning
confidence: 99%
“…25 Hence, the role of individual amino acids in the thermostability of BsDHFR was investigated here by site-directed mutagenesis by replacing them with the equivalent residues in MpDHFR. While apo-BsDHFR denatures at approximately 67 °C, 21 G. stearothermophilus can thrive at temperatures as high as 75 °C, 26 and additional environmental factors must help maintain the folded structure of BsDHFR in vivo .…”
mentioning
confidence: 99%